The World Conservation Strategy As A Dystopian Vision - Livingston, John R. (UnderCurrents: Journal of Critical Environmental Studies, 1989)
The World Conservation Strategy (WCS) was published in 1980 by the International Union for Conservation of Nature and Natural Resources (IUCN), the United Nations Environmental Programme (UNEP), the World Wildlife Fund (WWF), the Food and Agriculture Organization of the United Nations (FAO), and the United Nations Educational, Scientific and Cultural Organization (UNESC0). Its mandate was to establish a universal understanding of environmental problems and to secure the acceptance of planetary management goals. In the face of massive desertification, deforestation, the erosion of soils, the pollution of freshwater supplies, the extinction of species and many other ecological disasters, it seemed prudent to have one overall strategy for dealing with environmental ills. The authors of the WCS agreed that non-human resources had to be identified and protected in order to secure the integrity of ecosystems as well as our own future.